(untitled) (Progressive Agriculture, 2013)
To regenerate plantlets both directly and indirectly, different explants (cotyledon, hypocotyls, root tip and shoot tip) of mungbean were cultured on medium supplemented with different concentrations and combinations of BAP (0, 1.0 and 5.0 mgL-1) and NAA (0, 0.5 and 2.5 mgL-1)). Cotyledon explants performed best in callus induction (90.0%) at the combination of 1 mgL-1) BAP and 2.5 mgL-1)NAA for both the varieties (BINA mung 5 and BINA mung 7). The calli derived from cotyledon, hypocotyls and root tip were cultured in MS medium supplemented with different concentrations of Kn, BAP and/or NAA for shoot induction. Regeneration was achieved only from cotyledon calli at a frequency of 62.50% on 5 mgL-1) BAP and 0.05 mgL-1) NAA. Shoot tip cultured for direct regeneration in the same media containing 5 mgL-1) BAP and 0.05 mgL-1) NAA resulted in 90.0% shoot differentiation in BINA mung 7. The regenerated shoots rooted on MS medium with 0.2 mgL-1) NAA (90.0). DOI: http://dx.doi.org/10.3329/pa.v19i2.16908 Progress. Agric. 19(2): 13 - 19, 2008